A quantified description of the interactions between the native cardiovascular system and femoro‐femoral versus femoro‐axillary extracorporeal life support using descending thoracic aorta velocity time integral. Issue 7 (28th January 2019) - Andrei, Stefan; Tran‐Dinh, Alexy; Provenchere, Sophie; Lortat‐Jacob, Brice; Ghodbane, Walid; Montravers, Philippe; Longrois, Dan
Abstract: Extracorporeal life support (ECLS) is an important tool in managing severe cardio‐circulatory and respiratory failures. The axillary and the femoral sites are the most frequently used for arterial cannulation. There is no current evidence favoring one site over the other. We tested the hypothesis that the axillary and femoral arterial cannulation site may have different effects on left ventricular (LV) outflow. Seven patients with femoro‐axillary ECLS and 4 patients with femoro‐femoral ECLS were prospectively studied using the Pulse‐wave Doppler (PWD) velocity time integral (VTI) in the descending thoracic aorta (DTA VTI) at different short‐time variations of ECLS flow rates during the ECLS weaning process. The measurements were safe and feasible in all patients. We found a directly proportional correlation between DTA VTI and ECLS flow rate for femoro‐axillary cannulation ( P < 0.05) and an inversely proportional correlation in the case of femoro‐femoral cannulation ( P < 0.05). This is the first reported utilization of DTA VTI during ECLS that could improve our understanding of the LV‐aorta interactions in patients with ECLS. DTA VTI could be used as a tool, guiding weaning from ECLS.